Characterizing coherence with quantum observables - Suman Mandal; Marek Narozniak; Chandrashekar Radhakrishnan; Zhi-Qiang Jiao; Xian-Min Jin; Tim Byrnes (Physical Review Research, 2020)
We introduce a procedure based on quantum expectation values of measurement observables to characterize quantum coherence. Our measure allows one to quantify coherence without having to perform tomography of the quantum state and can be directly calculated from measurement expectation values. This definition of coherence allows the decomposition into contributions corresponding to the nonclassical correlations between the subsystems and localized on each subsystem. The method can also be applied to cases where the full set of measurement operators is unavailable. An estimator using the truncated measurement operators can be used to obtain lower bound to the genuine value of coherence. We illustrate the method for several bipartite systems and show the singular behavior of the coherence measure in a spin-1 chain, characteristic of a quantum phase transition.